(untitled) (Cadernos de Literatura em Tradução, 2021)
Semyon Nadson was a poet from Imperial Russia who died at the age of 24 and left a “contradictory legacy”, according to Paulo Bezerra. He inspired Rachmaninoff ’s compositions and had Bunin’s first published poem dedicated to him, but was criticized by Chukovsky and Mandelstam. Yet one thing is certain: he never stopped being read and mentioned by the Russians.